2021
DOI: 10.37934/arfmts.82.1.105112
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Using DBD Plasma for Application in Micro Combustors

Abstract: Dielectric-Barrier-Discharge (DBD) plasma actuators are one of the recent research topics that has caught worldwide attention. Plasma actuators are typically used in the aerospace field of study for their flow control and wide usage of different types of plasma actuators. DBD plasma actuator is an immobile actuator that able to be utilized for its flexibility and light weight parts. Due to the wide usage of DBD plasma, it is also able to be useful in the field of combustion in terms of air flow control. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The pH has a significant effect on the nature of the energy levels and, consequently, on the nature of electrical transitions in CQDs [117]. Besides, the PL intensity of CQDs produced from green tea decreased as the pH of the solution increased from 4.0 to 10.0 [118,119]. These studies indicated that the different PL intensities of the CQDs at different pH values might be related to the surface chemistry of the CQDs.…”
Section: Phmentioning
confidence: 86%
“…The pH has a significant effect on the nature of the energy levels and, consequently, on the nature of electrical transitions in CQDs [117]. Besides, the PL intensity of CQDs produced from green tea decreased as the pH of the solution increased from 4.0 to 10.0 [118,119]. These studies indicated that the different PL intensities of the CQDs at different pH values might be related to the surface chemistry of the CQDs.…”
Section: Phmentioning
confidence: 86%
“…Hydrogen is considered by many researchers as the fuel of the future as it does not emit carbon to the atmosphere during combustion. Other common renewable fuels suffer from combustion stability issues [24] and high emissions especially in reciprocating engines where combustion residence time is very limited [25]. However, hydrogen is considered an ideal fuel for such engines as it does not emit pollutants such as CO, while NOx emission can be eliminated by removing nitrogen sources [26].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the dielectric-barrier-discharge (DBD) plasma actuator's capability for air flow-based controlling in micro combustors with haze generator was evaluated. Continuously generated plasma has a maximal temperature of 90 C and has a minimal effect on the characteristics of the flow, according to the results [34]. Using CFD modelling, neon-oxygen was investigated for the stabilization of hydrogen ignition under standard ambient ingestion conditions.…”
Section: Introductionmentioning
confidence: 99%